NiáºÄm al-QurâÄn - Jannah, Miftahul (MAGHZA, 2018)
This paper intends to further examine the concept of NiáºÄm al-QurâÄn which is promoted by al-FarÄhi as the basis of its interpretation method. Thus, this paper places NiáºÄm al-QurâÄn as a material object and al-FarÄhi as its formal object. The significance of this study is not only to see the wealth of the method of interpretation of the Quran but as a form of the development of the interpretation method itself. In addition, it shows the pattern of development in the realm of interrelated interpretive methods. In this case, al-FarÄhi acknowledged what he was discussing - NiáºÄm al-QurâÄn - not something new, but he also emphasized the originality of the niáºÄm concept. The concept of NiáºÄm al-Quran for him is different from the concept of munÄsabah. NiáºÄm al-Quran surpasses and munÄsabah is part of it, not vice versa. From this concept, there appear wahdaniyah terms and âAmud. The first term is the difference between the two previous nomenclature and one of the three important elements in the concept of NiáºÄm al-Quran, besides tartÄ«b and tanÄsub. The second term is the central or central theme of each letter.